Effectiveness of interactive health promotion madule in improving knowledge attitude and practice on leptospirosis among town service workers in Kelantan - Daud, Aziah (Pusat Pengajian Kesihatan, 2016)
Seroprevalence, risk factors and the effectiveness of Interactive Health Promotion Module in improving knowledge, attitude and practice on leptospirosis among town service workers in Kelantan. Leptospirosis is presumed to be the most widespread re-emerging zoonotic disease of global importance affecting humans especially in tropical, subtropical and temperate zones. This study aims to determine the seroprevalence, knowledge, attitude and practice (KAP) and risk factors for leptospirosis and the effectiveness of Leptospirosis Interactive Health Promotion Module (LIHPM) among town service workers in Kelantan. In Phase One, a cross sectional study was conducted among 321 town service workers who fulfilled the study criteria and were randomly selected from four districts in Kelantan. Interviewer guided sessions using a validated questionnaire which consists of socio-demographic, occupational, environmental and recreational history as well as KAP questions were done with the subjects. Blood sample was taken from each subject for enzyme-linked immunosorbent assay (ELISA) and microscopic agglutination test (MAT). In Phase Two, an intervention study was done involving 69 ‘high risk for leptospirosis seropositivity’ subjects that were selected using Leptospirosis Risk Factor Checklist, in which 32 subjects from Kota Bharu Municipal Council were assigned in intervention group whereas 37 subjects from Tanah Merah, Kuala Krai and Gua Musang District Councils were assigned to control group. LIHPM was given to the intervention group while the control group received no intervention. The baseline KAP score was taken as the pre-intervention score while post-intervention KAP score was taken six weeks after intervention completion. All respondents were Malay race, predominantly males with the mean age of 40.6 (SD 10.28) years old. The mean duration of employment was 12.1 (SD 9.62) years. The overall seroprevalence of leptospirosis was 25.5% and the predominant serovar identified was Sarawak (59.8%). In the KAP assessment, most of the workers had moderate score for Knowledge domain and unsatisfactory score for Practice domain whereas for Attitude domain, the percentage of those who had satisfactory score (52%) were slightly higher than those with unsatisfactory score (48%). Occupational factors (worked overtime, contact with animal while working and rats sighting at worksite) and environmental factor (live ^200 meters from river) were identified as risk factors for leptospirosis exposure whereas recognized protective factors in this study were workers with older age, wearing boots while working and washed hand with soap after work. Six weeks after intervention completion, there was a significant increase of KAP mean score in intervention group (mean difference in intervention group was 34.31 for Knowledge domain (95% Cl: 25.52, 43.10; p<0.001), 27.34 for Attitude domain (95% Cl: 23.13, 31.55; p<0.001) and 26.74 for Practice domain (95% Cl: 22.56, 30.92; p<0.001)) compared to control group which had no significant increase of KAP mean score. The present study confirms that town service workers in Kelantan are high risk occupational group for leptospiral infection. There were a close association between leptospirosis seropositivity with sociodemographic, occupational and environmental factors. The workers’ KAP were unsatisfactory that justify the intervention program using LIHPM, which was found to be effective in improving KAP on leptospirosis among town service workers in Kelantan.